ANALISIS FAKTOR - FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN (STUDI EMPIRIS PADA PERUSAHAAN MANUFAKTUR SUB SEKTOR KIMIA YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2013 - 2018) - Kartino, Ferry Anggoro Prasetyo; Welas, Welas (Jurnal Akuntansi dan Keuangan, 2020)
The purpose of this research is to find the influence of sales growth, firm size, current ratio, debt to equity ratio and return on assets on the perceived firm value. In this Research Firm Value is proxied with price book value. This is a company sample in research sub petrochemical sectors who are enrolled in the Indonesia stock exchange a period of 2013-2018. The withdrawal of technique sample in this research purposive uses the method of sampling, where there are 7 the company chemical meet the criteria. The method of analysis was used in the study linear regression and the worship of idols with exclusively on the statistical package for the social science (SPSS) 20.0 version and microsoft excel for windows 2010 to know the influence of between the independent variable dependent on variables. The results of the testing of hypotheses this indicates that sales growth, firm size, current ratio, debt to equity ratio has not been affecting the Firm value. While return on assets influence by firm value.